Wandering spleen presenting in the form of right sided pelvic mass and pain in a patient with AD-PCKD: a case report and review of the literature - Yitagesu aberra shibiru; Sahlu wondimu; Wassie almaw (Journal of Medical Case Reports, 2024)
Abstract Background Wandering spleen is a rare clinical entity in which the spleen is hypermobile and migrate from its normal left hypochondriac position to any other abdominal or pelvic position as a result of absent or abnormal laxity of the suspensory ligaments (Puranik in Gastroenterol Rep 5:241, 2015, Evangelos in Am J Case Rep. 21, 2020) which in turn is due to either congenital laxity or precipitated by trauma, pregnancy, or connective tissue disorder (Puranik in Gastroenterol Rep 5:241, 2015, Jawad in Cureus 15, 2023). It may be asymptomatic and accidentally discovered for imaging done for other reasons or cause symptoms as a result of torsion of its pedicle and infarction or compression on adjacent viscera on its new position. It needs to be surgically treated upon discovery either by splenopexy or splectomy based on whether the spleen is mobile or not. Case presentation We present a case of 39 years old female Ethiopian patient who presented to us complaining constant lower abdominal pain especially on the right side associated with swelling of one year which got worse over the preceding few months of her presentation to our facility. She is primiparous with delivery by C/section and a known case of HIV infection on HAART. Physical examination revealed a right lower quadrant well defined, fairly mobile and slightly tender swelling. Hematologic investigations are unremarkable. Imaging with abdominopelvic U/S and CT-scan showed a predominantly cystic, hypo attenuating right sided pelvic mass with narrow elongated attachment to pancreatic tail and absent spleen in its normal position. CT also showed multiple different sized purely cystic lesions all over both kidneys and the pancreas compatible with AD polycystic kidney and pancreatic disease. With a diagnosis of wandering possibly infarcted spleen, she underwent laparotomy, the finding being a fully infarcted spleen located on the right half of the upper pelvis with twisted pedicle and dense adhesions to the adjacent distal ileum and colon. Release of adhesions and splenectomy was done. Her post-operative course was uneventful. Conclusion Wandering spleen is a rare clinical condition that needs to be included in the list of differential diagnosis in patients presenting with lower abdominal and pelvic masses. As we have learnt from our case, a high index of suspicion is required to detect it early and intervene by doing splenopexy and thereby avoiding splenectomy and its related complications.